Risk Factors for Nonadherence to Antihypertensive Treatment. Issue 6 (June 2017) - Gupta, Pankaj; Patel, Prashanth; Štrauch, Branislav; Lai, Florence Y.; Akbarov, Artur; Marešová, Věra; White, Christobelle M.J.; Petrák, Ondřej; Gulsin, Gaurav S.; Patel, Veena; Rosa, Ján; Cole, Richard; et al.
Abstract : Nonadherence to antihypertensive treatment is a critical contributor to suboptimal blood pressure control. There are limited and heterogeneous data on the risk factors for nonadherence because few studies used objective-direct diagnostic methods. We used high-performance liquid chromatography-tandem mass spectrometry of urine and serum to detect nonadherence and explored its association with the main demographic- and therapy-related factors in 1348 patients with hypertension from 2 European countries. The rates of nonadherence to antihypertensive treatment were 41.6% and 31.5% in the UK and Czech populations, respectively. Nonadherence was inversely related to age and male sex. Each increase in the number of antihypertensive medications led to 85% and 77% increase in nonadherence ( P <0.001) in the UK and Czech populations, respectively. The odds of nonadherence to diuretics were the highest among 5 classes of antihypertensive medications ( P ⩽0.005 in both populations). The predictive model for nonadherence, including age, sex, diuretics, and the number of prescribed antihypertensives, showed area under the curves of 0.758 and 0.710 in the UK and Czech populations, respectively. The area under the curves for the UK model tested on the Czech data and for the Czech model tested on UK data were calculated at 0.708 and 0.756, respectively. We demonstrate that the number and class of prescribed antihypertensives are modifiable risk factors for biochemically confirmed nonadherence to blood pressure–lowering therapy. Further development of discriminatory models incorporating these parameters might prove clinically useful in assessment of nonadherence in countries where biochemical analysis is unavailable.